Assessing the Effectiveness of Post-disaster Housing Reconstruction from the Flood Victims' Perspective: A Pilot Study - Adejoh Ahmodu Adaji,; Sulzakimin Mohamed,; Ibrahim Yakubu Ebenehi,; Richard Jimoh,; Ishiyaku Bala, (Journal of Technology Management and Business, 2019)
In any flooding, houses are the component that is most extensively damaged, and repeatedly represents the greatest portion of the loss in the overall impact of a disaster on the national economy. In October 2012, a flood devastated 14 States in Nigeria that included Kogi where safe actions on victims' rehabilitation, recovery and risk vulnerability reduction were swiftly taken through post-disaster housing reconstruction developments. However, the implementation of some of the resolutions was inadequately done due to non-availability of basic guidelines for the reconstruction processes. This research aims to develop a post-disaster housing reconstruction framework for flood victims in Nigeria. Fifty questionnaires were administered to the 2012 flood victims out of which 43 constituting 86% was valid for analysis using SPSS. This report reveals the results of the pilot study conducted before carrying out the main survey to collect information from target respondents. The pilot study shall help to minimise errors in the questionnaire, warrants the smooth running of the survey, ease the response rate, and offer a useful and valuable inquiry. The results include the descriptive statistics, reliability test, content and construct validity, the normality test, and factorability. The values of skewness and kurtosis were all within the recommended limit of -/+2, which indicates the normal distribution of all the constructs of the study. The summary of the reliability test for each construct of the post-disaster housing reconstructionquestionnaire, are Effectiveness of reconstruction strategies, 0.966; Resource mobilisation strategies, 0.772; Resilience strategies, 0.866, Reconstruction approaches, 0.816, Issues experienced, 0.944, and the Community satisfaction with reconstruction strategies have a value 0.902 for Cronbach alpha coefficient. The results are a positive indicator to use the instrument for the main survey.Keywords:Floods impact, Flood victims, Housing, Post-disaster housing reconstruction, Pilot study, Nigeria